METODE TASMI’ PADA HAFALAN AL-QUR’AN SANTRI PONDOK MODERN DARUSSALAM GONTOR KAMPUS 7 KALIANDA LAMPUNG SELATAN - Ahmad Hadi Fatahillah; Muslim Basyar; Anggi Septia Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Qur’an is the primary guidance for Muslims and must be read, memorized, and practiced properly. At Pondok Modern Darussalam Gontor Campus 7 Kalianda, South Lampung, the ability to read the Qur’an serves as an essential foundation before students enter the memorization stage. Based on initial observations, it was found that many students of class 1C had not yet been able to read the Qur’an correctly, particularly in terms of accuracy of tajwīd and makhārij al-ḥurūf. This condition potentially affects the quality of Qur’anic memorization. Therefore, the tasmī‘ method was implemented, emphasizing repeated activities of listening to and reciting Qur’anic verses. This study aims to describe the implementation of the tasmī‘ method in the Qur’anic memorization process of class 1C students at Pondok Modern Darussalam Gontor Campus 7 Kalianda. This research employed a qualitative approach, with data collected through interviews, observations, and documentation over a two-month period. The findings indicate that the tasmī‘ method not only improves students’ Qur’anic reading skills, particularly in tajwīd and pronunciation, but also contributes to producing more accurate, fluent, and stronger memorization due to being based on readings that adhere to proper tajwīd rules.